Into Africa : a transnational history of Catholic medical missions and social change - Wall, Barbra Mann (Rutgers University Press, 2015)
In Into Africa, Barbra Mann Wall offers a transnational history that explores the intersection of religion, medicine, gender, race, and politics in sub-Saharan Africa, focusing on the years following World War II. The book highlights the importance of transnational partnerships, using the stories of four groups of European and American nuns to enhance our understanding of medical mission work and global change.